APLIKASI TEKNOLOGI FERMENTASI LIMBAH SAGU UNTUK MENUNJANG KETERSEDIAAN PAKAN SAPI DI DESA PUPUAN TEGALLALANG GIANYAR BALI - Roni, N.G.K.; Kusmiyarti, T.B.; Siti, N.W.; Karyati, N.K. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p13, 2018)
Community service activities that aim to transferring fermentation technology to make silage feed to support of breeding Balinese cattle in Pupuan Village, Tegallalang District, Gianyar Regency. The methods applied in the community empowerment are as follows: (1) Participatory coordination and communication with livestock breeding groups to formulate programs planning, operation and evaluation; (2) Counseling to build community perceptions and understanding of innovations or programs implemented; (3) Training and simulation of applied ipeks transferred to the community; (4) Assistance is regular and continuous meetings between assistants with target communities to transferred science and technology can be implemented independently by the community. The results show that dissemination activities through IbW program in Pupuan Village, Tegallalang district, Gianyar Regency can take place well indicated by active participation and high adoption of science and technology. The active participation of partners in all technological dissemination activities is quite high, ie the presence of group members at the time of counseling and training reaches 100%, who ask/express opinion 60%, and try to practice 68%. The ability of science and technology adoption and partner initiatives to produce products independently is high enough, at 60%